Perception on Environmental Innovations and Smart City Projects among Residents in Lagos Metropolis, Nigeria (International Journal of Built Environment and Sustainability, 2025)
The increasing process of urbanization and swift growth in population in many nations has continued to attract researchers’ attention. Studies in this direction are looking on how to create appropriate strategies so that the built environment can continue to be cool, habitable and sustainable. The proposition of Green Infrastructure (GI) has been advocated in various nations as a means to revitalize depleted green areas in the environment and provide numerous ecosystem services and benefits to man. This study assessed perception on environmental innovations and smart city projects among selected residents in Lagos Metropolis, Nigeria. A multi-stage sampling technique was employed to select 1144 residents who participated in a questionnaire survey. The results of the descriptive statistics and independent t-test analysis reveal that 72.0% and 57.1% of residents were aware of the GI and smart city innovation projects respectively in the study area. About 66.0% were not interested in collecting information from the smart information/advertisement boards. While there is no significant difference in the perception of the effect of GI on environmental quality from smart city projects by male and female participants examined. With suitable governmental policies, increased awareness campaigns, and expansion of GI facilities and smart city technological innovations, Lagos state can continue to develop sustainably which will in turn have multiple effects on the quality of life of city dwellers in Lagos and similar settings.
Keywords: Green Infrastructure, Innovation, Smart city, Urban Environment, Urbanization